2020
DOI: 10.1080/03007995.2020.1776232
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Unified Classification System applied to periprosthetic femur fractures: a comparison with the Vancouver system

Abstract: Objective: The Unified Classification System (UCS) presents itself as an evolution of the Vancouver Classification (VCS) for the evaluation of periprosthetic fractures of the proximal femur (PPF). The aim of our study was to evaluate the interobserver and intraobserver reliability, with the purpose of highlighting any loss of reproducibility or validity of the new classification system, compared to the previous one, when applied to the proximal femur. Material and Methods:We tested the interobserver and intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In order to provide evidence about the safety and efficacy of UCS we compared the validity and reliability of both classification systems, evaluating their use on the same population sample. This study demonstrated how, in VCS and UCS, validity and reproducibility are at least equal 1 .…”
Section: Letter To the Editormentioning
confidence: 57%
“…In order to provide evidence about the safety and efficacy of UCS we compared the validity and reliability of both classification systems, evaluating their use on the same population sample. This study demonstrated how, in VCS and UCS, validity and reproducibility are at least equal 1 .…”
Section: Letter To the Editormentioning
confidence: 57%
“…Periprosthetic femoral fractures (PFFs) are one of the main causes for revision after hip arthroplasty, with an incidence ranging from 6.6-18% [1][2][3][4]. Furthermore, the incidence of periprosthetic femoral fractures is expected to increase by up to 4.6% per decade [1,[5][6][7][8] to a cumulative incidence of almost 5% [9]. PFFs can have detrimental consequences for the patient with a mortality rate of up to 11% within 1 year after surgical treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…"C" cases describe fractures distinct below the prosthesis stem, the prosthesis is considered stable [12]. It has been demonstrated to be valid and reproducible [1,14]. Finally, it also provides treatment recommendations [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed it to be reliable and valid. More recently, De Meo et al 13 reassessed the reliability and validity of the UCS by comparing the results of the VCS in PPFF in 40 patients. The results showed that the UCS is reliable and had a slightly higher validity when compared with the VCS.…”
mentioning
confidence: 99%
“…When applied to the proximal femur, however, the UCS fails to resolve the VCS controversy, linked to the difficulty of evaluating the stem's stability in type B fractures. Another limitation is the absence of some specific fracture pattern in PPFF [13][14][15] . Due to this reason, Huang et al 15 modified the UCS for PPFF by adding two new B2 subtypes and a new category to encompass stem fracture alone or accompanied by PPFF.…”
mentioning
confidence: 99%